The niobium oxoazides [NbO(N3)3], [NbO(N3)3·2CH3CN], [(bipy)NbO(N3)3], Cs2[NbO(N3)5] and [PPh4]2[NbO(N3)5]. Issue 26 (20th May 2016) - Haiges, Ralf; Vasiliu, Monica; Dixon, David A.; Christe, Karl O.
Abstract : Niobium oxotriazide, [NbO(N3 )3 ], was prepared from [NbOF3 ] and Me3 SiN3 and in subsequent reactions converted into oxoazidoniobates. Abstract : Niobium oxotriazide, [NbO(N3 )3 ], was prepared in a fluoride–azide exchange reaction between [NbOF3 ] and an excess of Me3 SiN3 in SO2 solution. In acetonitrile solution, the fluoride–azide exchange resulted in the isolation of the adduct [NbO(N3 )3 ·2CH3 CN]. The subsequent reaction of [NbO(N3 )3 ] with 2, 2′-bipyridine (bipy) resulted in the isolation of the bipyridine adduct [(bipy)NbO(N3 )3 ]. The pentaazido anion [NbO(N3 )5 ] 2− was obtained by the reaction of [NbO(N3 )3 ] with two equivalents of ionic azide. The novel niobium oxoazides were fully characterized by their vibrational spectra, impact, friction and thermal sensitivity data and, in the case of [(bipy)NbO(N3 )3 ], Cs2 [NbO(N3 )5 ], and [PPh4 ]2 [NbO2 (N3 )5 ] by their X-ray crystal structures.